Resuscitating Sungai Alur Ilmu as a vibrant campus community space At Universiti Kebangsaan Malaysia, Bangi, Selangor - Elias, Nur Amalina (2018)
As an important subsystem of the built environment, river within campus offers many kinds of ecological services which benefit the campus community. However, with the acceleration of urbanization and human activities, the river pollution problem are becoming more and more critical. This project proposal described the resuscitation of Sungai Alur Ilmu located at Universiti Kebangsaan Malaysia, Bangi, Selangor. It summarized the research on river pollution control and remediation. The aim of the project is towards resuscitating Sungai Alur Ilmu as a vibrant campus community space through the implementation of the ecological approach. The main concern about this project is the impact of urban development and human activities on the river's health. Through several processes that have been discussed in this paper, Sungai Alur Ilmu can be revolutionized into a vibrant campus recreational and educational space. From the data analysis, the main conflict of Sungai Alur Ilmu can be concluded into two major challenges which are the environmental and social aspect; degradation of the water quality and static atmosphere that reduced the human quality of life within the campus. With Sungai Alur Ilmu as the main subject of the project interest, the vision and strategy made are focusing on the campus user and the river's ecology. Based on the advances of river remediation, this paper concluded the approaches to alleviate the river pollution problem that the biological-ecological remediation should be utilized as the primary technique. While improving the river's health, the potential spaces along the river are enhanced according to campus community needs complimenting the identity of surrounding Sungai Alur Ilmu as an institution.